The genetic diagnosis of rare endocrine disorders of sex development and maturation: a survey among Endo-ERN centres. Issue 12 (14th November 2022) - Persani, Luca; Cools, Martine; Ioakim, Stamatina; Faisal Ahmed, S; Andonova, Silvia; Avbelj-Stefanija, Magdalena; Baronio, Federico; Bouligand, Jerome; Bruggenwirth, Hennie T; Davies, Justin H; De Baere, Elfride; Dzivite-Krisane, Iveta; et al.
Abstract : Differences of sex development and maturation (SDM) represent a heterogeneous puzzle of rare conditions with a large genetic component whose management and treatment could be improved by an accurate classification of underlying molecular conditions, and next-generation sequencing (NGS) should represent the most appropriate approach. Therefore, we conducted a survey dedicated to the use and potential outcomes of NGS for SDM disorders diagnosis among the 53 health care providers (HCP) of the European Reference Network for rare endocrine conditions. The response rate was 49% with a total of 26 HCPs from 13 countries. All HCPs, except 1, performed NGS investigations for SDM disorders on 6720 patients, 3764 (56%) with differences of sex development (DSD), including 811 unexplained primary ovarian insufficiency, and 2956 (44%) with congenital hypogonadotropic hypogonadism (CHH). The approaches varied from targeted analysis of custom gene panels (range: 11–490 genes) in 81.5% of cases or whole exome sequencing with the extraction of a virtual panel in the remaining cases. These analyses were performed for diagnostic purposes in 21 HCPs, supported by the National Health Systems in 16 cases. The likelihood of finding a variant ranged between 7 and 60%, mainly depending upon the number of analysed genes or criteria used for reporting, most HCPs also reporting variants of uncertain significance. These data illustrate the status of genetic diagnosis of DSD and CHH across Europe. In most countries, these analyses are performed for diagnostic purposes, yielding highly variable results, thus suggesting the need for harmonization and general improvements of NGS approaches.